Astor Piazzolla : a memoir - Piazzolla, Astor; Gonzales, Fernando, 1954-; Gorin, Natalio (Portland, Oregon : Amadeus Press, 2001)
"Astor Piazzolla (1921-1992), brilliant, iconoclastic tango musician and composer, has become a national hero in Argentina and a cult figure for classical and jazz lovers worldwide, but only after a lifetime of controversy and struggle. Piazzolla dared to revitalize, if not revolutionize, tango - to hear in the music possibilities that others couldn't, or wouldn't, imagine. He revised the harmonic language of tango by incorporating the influences of Ravel, Debussy, and Messiaen, along with a sure sense of cool jazz. And he had the audacity to compose tangos that were not for dancing, tangos of such melodic and rhythmic complexity that both worlds, classical and popular, would ultimately claim him as their own." "Among the firsthand observations by the loving colleagues who knew Piazzolla well are those of his lyricist Horacio Ferrer, his fellow musicians, and jazz musician Gary Burton; Burton's recollections appear in this volume for the first time. Translator Fernando Gonzalez has annotated the Amadeus edition for all those who are rediscovering Astor Piazzolla. With such renowned musicians as Yo-Yo Ma and Gidon Kremer performing Piazzolla's works on their classical programs, Piazzolla's audience only continues to grow."--BOOK JACKET.
Includes discography (pages 220-248), bibliographical references (pages 252-253), and index.
Keywords: Piazzolla, Astor; Bandoneon players -- Argentina -- Biography; Composers -- Argentina -- Biography; bandoneon; diskografiat; harmonikka; henkilöhistoria; historia; muusikot; säveltäjät; tangot (sävellykset); Argentiina